2020
DOI: 10.1021/acs.macromol.0c02046
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Primary Structure of Syndiotactic Poly(Methyl Methacrylate) on the Inclusion Complex Formation with [60]Fullerene: Robustness of the Helix against Primary Structural Errors

Abstract: Syndiotactic poly­(methyl methacrylate) (st-PMMA) is known to form an inclusion complex with fullerenes in toluene. We investigated in detail the influence of the primary structure of st-PMMA, such as the molecular weight and stereoregularity, on the inclusion complex formation with C60. The formation of an inclusion complex with C60 was accompanied by gelation that occurred in toluene by using st-PMMAs with an rr content of 89% and an M n of over 7.8 × 103 in the polymer, with C60 concentrations of 10 and 2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…q 4 at 1.26 Å –1 and q 5 at 1.41 Å –1 can be assigned to the distance ( d 4 = 5.0 Å) between C 60 and the st -PMMA helix and packing distance ( d 5 = 4.5 Å) of side groups of st -PMMA, respectively. Kawauchi et al reported that the formation of the st -PMMA/C 60 inclusion complex can occur at rr content of st -PMMA above 89% . Our structural characterization first indicates that st -PMMA with a lower rr (79%) can still wrap C 60 s to form the helical structure, where the C 60 s align into the 1D molecular wire with CN = 2, as illustrated in Figure f.…”
Section: Results and Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…q 4 at 1.26 Å –1 and q 5 at 1.41 Å –1 can be assigned to the distance ( d 4 = 5.0 Å) between C 60 and the st -PMMA helix and packing distance ( d 5 = 4.5 Å) of side groups of st -PMMA, respectively. Kawauchi et al reported that the formation of the st -PMMA/C 60 inclusion complex can occur at rr content of st -PMMA above 89% . Our structural characterization first indicates that st -PMMA with a lower rr (79%) can still wrap C 60 s to form the helical structure, where the C 60 s align into the 1D molecular wire with CN = 2, as illustrated in Figure f.…”
Section: Results and Discussionmentioning
confidence: 59%
“…Kawauchi et al reported that the formation of the st-PMMA/C 60 inclusion complex can occur at rr content of st-PMMA above 89%. 29 Our structural characterization first indicates that st-PMMA with a lower rr (79%) can still wrap C 60 s to form the helical structure, where the C 60 s align into the 1D molecular wire with CN = 2, as illustrated in Figure 2f. Furthermore, the OM micrographs in Figure 2c,d reveal that as the transparent st-PMMA/C 60 complex film is heated to over 190 °C, C 60 crystals form in the st-PMMA/C 60 complex film resulting in the diffraction feature of fcc packing (Figure 2e).…”
Section: ■ Introductionmentioning
confidence: 83%
See 2 more Smart Citations